Irrigation and enhanced soil carbon input effects on below-ground carbon cycling in semiarid temperate grasslands - Xiao, Chunwang (The New phytologist, 2007)
Global climate change is generally expected to increase net primary production, resulting in increased soil carbon (C) inputs. To gain an understanding of how such increased soil C inputs would affect C cycling in the vast grasslands of northern China, we conducted a field experiment in which the responses of plant and microbial biomass and respiration were studied. Our experiment included the below-ground addition of particulate organic matter (POM) at rates equivalent to 0, 60, 120 and 240 g C m(-2), under either natural precipitation or under enhanced precipitation during the summer period (as predicted for that region in recent simulations using general circulation models). We observed that addition of POM had a large effect on soil microbial biomass and activity and that a major part of the added C was rapidly lost from the system. This suggests that microbial activity in the vast temperate grassland ecosystems of northern China is energy-limited. Moreover, POM addition (and the associated nutrient release) affected plant growth much more than the additional water input. Although we performed no direct fertilization experiments, the response of plant productivity to POM addition (and associated release of nutrients) leads us to believe that plant productivity in the semiarid grassland ecosystems of northern China is primarily limited by nutrients and not by water